(597) planning of Production in Socialist Industry (Part I: Instruments and Indicators), (Part II: Investigation of demand and market تخطيط الإنتاج في الصناعة الاشتراكية (الجزء الأول: الأدوات والمؤشرات)، (الجزء الثاني: دراسة الطلب والسوق) - Sack, Kurt; Linsel, Hermann (INP, 2024)
part I discusses the importance of industrial development in the national economy, highlighting its vital role in promoting economic growth and creating job opportunities. It addresses the instruments and indicators of production planning, which include effective strategies for improving production efficiency. Additionally, it emphasizes the indicators used in production planning to evaluate industrial performance, including the assessment of industrial production and the development of an indicator system that helps achieve production goals. Such planning is essential for ensuring sustainable industrial growth and achieving economic development. Part II This study discusses the procedures of production planning, focusing on the investigation of demand and market. It begins by identifying the contents of the investigation, aiming to understand consumer needs and market trends. It also covers the procedures involved in this investigation, including the continuous observation of demand and market, which helps track changes in consumer preferences. Additionally, a comprehensive analysis of demand and market is conducted, involving the study of data to identify patterns and trends. This analysis is essential for making informed production decisions that support success in the marketplace. Part III addresses the planning of productive capacity, starting with the definition of capacity concepts and their significance in enhancing industrial efficiency. It discusses the procedures for calculating productive capacity, including the methodical approaches used in these calculations. Additionally, it covers the effective utilization of productive capacity to maximize resource benefits. Moreover, it explores production planning through mathematical methods while considering various given conditions. The section concludes with remarks emphasizing the importance of precise planning to ensure the achievement of production objectives.